Crystal-structure analysis, Raman spectroscopy, dielectric measurements, magnetic and optical properties of Cr3+–Ni2+-substituted Co2Y-type barium hexaferrites. (January 2022) - Carol T, Tchouank Tekou; Mohammed, J.; Batoo, Khalid Mujasam; Mukhtar, G.; Puzon Labis, Joselito; Raslan, Emad H.; Hadi, Muhammad; Srivastava, A.K.
Highlights: Sol-gel synthesized Cr 3+ –Ni 2+ substituted Co2 Y-type Barium hexaferrites. Rietveld refinement of the crystal structure using Fullprof software. Grain-boundary contributions as the dominant factor causing the dielectric properties. Synthesized samples showing hexagonal plate-like morphologies. Abstract: The Co2 Y-type barium hexaferrite Ba2−2 x Cr x Ni x Co2 Fe12 O22 ( x = 0.0, 0.1, 0.15) was synthesized using the sol–gel auto-combustion technique. The formation phase of the Y-type hexaferrites was observed using X-ray diffraction (XRD) analysis. Fourier-transform infrared (FTIR) analysis confirms the formation of Y-type hexaferrites. Field-emission scanning electron microscopy (FESEM) reveals particles with hexagonal plate-like morphologies. The optical band gap of the prepared samples lies between 0.74 and 2.16 eV. The coercivity values of the prepared samples demonstrate their soft-magnetic nature. Dielectric analyses show the influence of the dopant ions on the dielectric parameters of the prepared samples. Impedance spectroscopy using a Nyquist plot shows that most of the dielectric response results from grain-boundary contributions. Graphical abstract: Image, graphical abstract